Variações temporais de comunidades e estratégias de crescimento de populações arbóreas ao longo de um gradiente altitudinal - Morelli, Mariana Caroline Moreira (2017)
The aim of this paper was to analyze the structural changes in a tree community of semideciduous forest, located in the Mindurí, Minas Gerais, during the period of 5 years (2010-2015) to monitor and detect patterns associated with altitudinal variation in which the community is submitted. To this end, it sought to answer the following question: how does the structural dynamics of the forest vary along the altitudinal gradient? In 2010, ecological studies were started in the area through a structural survey of the tree community, with allocation of 30 permanent plots of 10x40 m, along five altitudinal levels, totaling a sampling of 1.2 ha. All living arboreal individuals, who met the inclusion criterion (CAP ≥ 15.7 cm), received numbered almanac labels and were measured in circumference. In 2015, the monitoring inventory, where the surviving individuals were measured, the counts dead and the recruits incorporated into the sampling. Structural modifications were analyzed by obtaining dynamics rates related to the demography of individuals and biomass at each altitudinal elevation. There were no consistent trends in changes in forest structure during the 5-year interval in the altitudinal gradient. The community at 1200 m altitude had the lowest rates of dynamics if differentiated from the others and the community at 1500 m was differentiated by having a higher rate of recruitment. The others presented similar responses, suggesting that the forest is adapted to the environmental conditions of each altitude altitudinal. The second article analyzed six populations of Asiposperma olivaceum Müll. Arg., A species that differs widely along the altitudinal gradient. Leaf area, specific leaf area, leaf dry matter, leaf thickness, petiole size and diameter were measured. The basic density of the wood was calculated as well as counting and measurements of the widths of the growth rings. The growth strategies were characterized by measurements of leaf and stem attributes, in addition, diametric increase rates were accumulated to construct growth curves. Rapid growth strategies were observed at the lower levels, as well as slower growth rhythm was found at the higher levels, suggesting that with increasing altitude there is a greater investment of resources in wood density, thick and durable leaves. In the multivariate analysis the characteristics of leaf thickness, petiole diameter, material content and wood density clearly showed associations and larger axes facing the 1300, 1400 and 1500 m coordinates. Differences in traits among individuals reflect variation in growth strategies. These different strategies will help in understanding the changing species distribution under predicted climate change scenarios.